2016
DOI: 10.1124/mol.116.106963
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Protein Signaling 10 (Rgs10) Expression Is Transcriptionally Silenced in Activated Microglia by Histone Deacetylase Activity

Abstract: RGS10 has emerged as a key regulator of proinflammatory cytokine production in microglia, functioning as an important neuroprotective factor. Although RGS10 is normally expressed in microglia at high levels, expression is silenced in vitro following activation of TLR4 receptor. Given the ability of RGS10 to regulate inflammatory signaling, dynamic regulation of RGS10 levels in microglia may be an important mechanism to tune inflammatory responses. The goals of the current study were to confirm that RGS10 is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 51 publications
0
37
0
Order By: Relevance
“…A number of HDAC inhibitors have been tested in different pain models and it has been shown that they have analgesic effects through different mechanisms ( Chiechio et al, 2009 , 2010 ; Bai et al, 2010 ; Zhang et al, 2011 ; Denk et al, 2013 ; Matsushita et al, 2013 ; Onofrj et al, 2013 ; Ximenes et al, 2013 ; Chen et al, 2014 ; Kukkar et al, 2014 ; Zammataro et al, 2014 ; Capasso et al, 2015 ; Cao et al, 2016 ; Tao et al, 2016 ; Alqinyah et al, 2017 ; Fork et al, 2017 ; Lin et al, 2017 ). We first demonstrated that HDAC inhibitors have analgesic properties via the upregulation of the metabotropic glutamate receptor type-2 ( Chiechio et al, 2009 , 2010 ; Onofrj et al, 2013 ), an inhibitory receptor whose activation or upregulation mediates analgesia ( Chiechio et al, 2002 , 2009 , 2010 ; Onofrj et al, 2013 ; Zammataro et al, 2014 ; Chiechio, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of HDAC inhibitors have been tested in different pain models and it has been shown that they have analgesic effects through different mechanisms ( Chiechio et al, 2009 , 2010 ; Bai et al, 2010 ; Zhang et al, 2011 ; Denk et al, 2013 ; Matsushita et al, 2013 ; Onofrj et al, 2013 ; Ximenes et al, 2013 ; Chen et al, 2014 ; Kukkar et al, 2014 ; Zammataro et al, 2014 ; Capasso et al, 2015 ; Cao et al, 2016 ; Tao et al, 2016 ; Alqinyah et al, 2017 ; Fork et al, 2017 ; Lin et al, 2017 ). We first demonstrated that HDAC inhibitors have analgesic properties via the upregulation of the metabotropic glutamate receptor type-2 ( Chiechio et al, 2009 , 2010 ; Onofrj et al, 2013 ), an inhibitory receptor whose activation or upregulation mediates analgesia ( Chiechio et al, 2002 , 2009 , 2010 ; Onofrj et al, 2013 ; Zammataro et al, 2014 ; Chiechio, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of RGS10 in microglia amplifies production of inflammatory cytokines, such as tumor necrosis factor a (TNFa) and interleukin 1b, and enhances microglia-induced neurotoxicity triggered by the toll-like receptor (TLR) ligand lipopolysaccharide (LPS) (Lee et al, 2011). Reciprocally, activation of microglia by LPS induces epigenetic silencing of RGS10, which we predict serves to amplify inflammatory signaling (Alqinyah et al, 2017). In addition to its anti-inflammatory role in microglia, RGS10 also regulates survival of ovarian cancer cells, and loss of RGS10 induces chemoresistance in ovarian cancer cells (Hooks et al, 2010;Ali et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Microglial RGS10 suppresses the release of TNFa and other inflammatory cytokines following inflammatory triggers (Lee et al, 2008) and plays a protective role against microglia-induced neurodegeneration of dopaminergic neurons (Lee et al, 2011). Reciprocally, microglial activation by either LPS or TNFa suppresses the expression of RGS10 and reduces RGS10 protein levels by approximately 50%-70% for approximately 48 hours (Alqinyah et al, 2017). Thus, endogenous RGS10 silencing mechanisms likely serve to amplify and enhance inflammation in a feed-forward mechanism that sustains a continuous cycle of RGS10 suppression and enhanced production of inflammatory cytokines (Lee et al, 2008;Alqinyah et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Liu, Chatterjee, & Fisher, 2002;Martin-McCaffrey et al, 2005;Nixon, Grenningloh, & Casey, 2002;Sivori et al, 2019) and cell proliferation (Chi et al, 2017;Madrigal et al 2017;Scherer, Cain, Kanai, Kaltenbronn, & Blumer, 2017;Tso et al, 2010;Vivot et al 2016;Willard et al, 2007;Yang and Li 2007). Members of the RGS family may additionally regulate transcriptional pathways (Alqinyah et al, 2017;Feigin and Malbon 2007;Gaspari et al, 2018;Ikeda et al, 1998;Shimizu et al 2003;Z. Liu & Fisher, 2004) and chromatin function (Alqinyah et al, 2017;Branch & Hepler, 2017;Z.…”
Section: Downloaded Frommentioning
confidence: 99%